Comprehensive energy-saving control of asynchronous motor based on penalty functio - LI Jianhong; ZHOU Lawu; XUE Zhengshan (Gong-kuang zidonghua, 2014)
In view of problem of non-ideal control effect of energy-saving of existing asynchronous motor, the paper proposed a design scheme of comprehensive energy-saving control device based on penalty function, and established integrated optimization model of energy-saving control device. The device uses dynamic voltage regulation technology in frequency-conversion speed-regulation, and can dynamically adjust terminal voltage and frequency of the motor; it adopts penalty function algorithm to optimize power output, so as to make frequency-conversion speed-regulation system of the motor operate in the best mode, and achieve goal of energy-saving. The Matlab simulation results show that the comprehensive energy-saving control device has advantages of voltage and speed regulating energy-saving, and has good energy-saving effect.